Standard reference values for the shock index during pregnancy. Issue 1 (October 2016) - Borovac-Pinheiro, Anderson; Pacagnella, Rodolfo C.; Morais, Sirlei S.; Cecatti, Jose G.
Abstract: Objective: To assess variation in the shock index (SI; heart rate divided by systolic blood pressure) during pregnancy. Methods: In a retrospective cohort study, data were assessed from the medical records of women with low-risk pregnancies who attended a primary healthcare unit for prenatal care in Campinas, Brazil, between January 2012 and December 2013. The means, standard deviations, and percentiles of SI values were calculated for different pregnancy lengths, stratified by body mass index (BMI) and maternal age. Results: In total, 192 pregnant women with 1097 measurements were included. The mean SI values ranged from 0.756 ± 0.127 at 12 weeks or fewer to 0.831 ± 0.144 at 28–32 weeks. There was an increase in values in the second trimester and beginning of the third, followed by a decrease at term. The percentile distribution ranged from 0.522 (2.5th percentile) to 1.190 (97.5th percentile). SI values showed a trend toward lower values with increasing BMI. Regression analysis showed that BMI was the factor that most influenced the data. Conclusion: Reference ranges were established for SI values, which showed small variations throughout pregnancy and slightly higher values than the general population.